Modeling the effect of elastane linear density, fabric thread density, and weave float on the stretch, recovery, and compression properties of bi-stretch woven fabrics for compression garments. Issue 3 (3rd March 2016) - Maqsood, Muhammad; Hussain, Tanveer; Malik, Mumtaz Hasan; Nawab, Yasir
Abstract : The aim of this study was to investigate the effect of elastane linear density, thread density, and weave float on the stretch, recovery, and compression properties of bi-stretch woven fabrics for compression garments. Fabric samples were produced using elastane core-spun cotton yarns both in the warp and weft. The elastane linear density, fabric thread density, and weave float size were used as input variables while fabric contraction, subgarment pressure, fabric stretch, and recovery were taken as response variables. Two different elastane linear densities, i.e. 44 and 78 dtex, two different thread densities, and three different weave designs, i.e. 1/1 plain, 2/2 z-twill, and 3/3 z-twill were used. The results of fabric samples were analyzed in Minitab statistical software. The coefficients of determinations ( R -sq values) of the regression equations showed good prediction ability of the developed statistical models. The findings of the study may be helpful in deciding appropriate manufacturing specifications of bi-stretch fabrics to attain specific stretch, recovery, and compression properties.